Review On Secure Anti-Collusion Data Sharing For Dynamic Group In The Cloud (International Journal of Engineering and Computer Science, 2016)
vBenefited from cloud computing, users can achieve an effective and economical approach for data sharing among group members in the cloud with the characters of low maintenance and little management cost.   In multiuser cloud computing there may be a major problem to securely share documents. Frequent change of membership, challenging issues to prevent the system from collusion attack, to secure the system from the revoked user. In this paper we propose a secure data forwarding mechanism for dynamic member. Firstly, we propose a cloud system in which no of server should be present any user must store the file in any server. Secondly, the file must upload in no of blocks in the same server. Thirdly, the data forwarding; the uploading user may forward the data to the requested user in the cloud. If the member of cloud should exchange the information to one another they forward the data to the id of the members. Other member can’t access file in the cloud without permission of file up loader. By this scheme the revoked user can’t access the original data. in this scheme all the time the cloud member get permission from the up loader member for access the information at the time of file transfer up loader know the requested id he provide the server id and no of block to the downloader. The file should store in the server in maximum four no of block i.e. file is splitting in four parts. Each two block should be encrypted and store in the server. RSA and MD-5 encryption algorithm should be used for encrypting four blocks. In multiuser environment user doesn’t know which encryption will used for which block.